Factors influencing the Poverty Depth Index in West Sumatra Province through Panel Data Regression Analysis - Helma; Mutia Syifa (Mathematical Journal of Modelling and Forecasting, 2023)
The poverty depth index is one of the measures that can be used in measuring the poverty level in a region well. This is because the poverty depth index measures the depth of poverty by focusing on the expenditure gap of the poor against the poverty line. Based on BPS West Sumatra data for 2017-2022, the IKK which was initially at 1,00 rose to 1,04 in 2018, in 2019 it fell to 0,94, in 2020 it fell to 0,92, but in 2021 it rose to 1,04 and fell to 0,8 in 2022. The dynamics that occur in the IKK show that the government's efforts in dealing with poverty problems have not been optimal. Therefore, a study was conducted to determine the model and factors that affect the IKK in West Sumatra Province using panel data regression analysis. After the research was conducted, the best estimation model obtained was the Fixed Effect Model (FEM). The factors that affect IKK in 2017-2022 are average per capita expenditure and human development index.